Photodynamic Therapy in Endodontics: A Helpful Tool to Combat Antibiotic Resistance? A Literature Review - Haitham Abdelkarim-Elafifi; Isabel Parada-Avendaño; Josep Arnabat-Dominguez (MDPI AG, 2021)
Background: Antibiotic resistance has become a growing global problem where overprescription is a contributing factor for its development. In the endodontics field, complementary treatments, such as antimicrobial photodynamic therapy (aPDT), have been described to eliminate residual bacteria from the root canal space and reduce complications. The aim of this review is to describe the literature evidence up to now regarding the advantages, efficiency, and clinical outcomes of this therapy in endodontics as a possible tool to combat antibiotic resistance. Methods: A review of the literature from 2010 to 2021 was carried out using the PubMed and Web of Science databases. Two steps were taken: First, articles were compiled through the terms and MeSH terms "Photochesdmotherapy" and "endodontics." Then, a second search was conducted using "photodynamic therapy" and "antibiotic resistance" or "drug resistance, microbial." Results: A total of 51 articles were included for evaluation: 27 laboratory studies, 14 reviews, and 10 clinical studies. Laboratory studies show that aPDT achieves significant bacterial elimination, even against antibiotic-resistant species, and is also effective in biofilm disruption. Clinical studies suggest that aPDT can be considered a promising technique to reduce bacterial complications, and reviews about the issue confirm its advantages. Conclusion: The benefits of aPDT in reducing complications due to its antibacterial effects means a possible decrease in systemic antibiotic prescription in endodontics. In addition, it could be an alternative to local intracanal antibiotic therapy, avoiding the appearance of possible antibiotic resistance, as no bacterial resistance with aPDT has been described to date.